1997
DOI: 10.1002/(sici)1099-0518(19970130)35:2<227::aid-pola4>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Binary frontal polymerization: A new method to produce simultaneous interpenetrating polymer networks (SINs)

Abstract: We report a new method for the preparation of a simultaneous interpenetrating polymer network (SIN) using a thermal propagating front of two independent and noninterfering polymerization mechanisms. The system consists of the free radical crosslinking of triethylene glycol dimethacrylate (TGDMA) and the amine/BCl3 · amine curing of diglycidyl ether of bisphenol A (DGEBA). The front velocity dependence on the percentage of each monomer shows a minimum at 45% TGDMA. Temperature profile measurements indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
108
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 0 publications
1
108
0
Order By: Relevance
“…Previous investigations have focused on dual curing modes in acrylate/vinyl ether [5,6], vinyl ether/epoxy [7,8], or acrylate/epoxy systems [9][10][11], providing tailorable mechanical properties and improved polymerization kinetics. Investigations have shown the importance of monomer composition in controlling the final conversion and the polymer glass transition temperature [4], as well as the importance of cure sequence in acrylate/epoxy hybrid systems on the final resin conversion and morphology [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have focused on dual curing modes in acrylate/vinyl ether [5,6], vinyl ether/epoxy [7,8], or acrylate/epoxy systems [9][10][11], providing tailorable mechanical properties and improved polymerization kinetics. Investigations have shown the importance of monomer composition in controlling the final conversion and the polymer glass transition temperature [4], as well as the importance of cure sequence in acrylate/epoxy hybrid systems on the final resin conversion and morphology [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the nineties, a great deal of work has been done mainly by Pojman et al who studied macrokinetics and dynamics [8][9][10][11][12] and new frontally polymerizing systems [13][14][15]; Morbidelli et al suggested the application of FP to the preparation of copolymers [16] and blends [17]; Washington and Steinbock published on the preparation of hydrogels by FP [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Pojman et al developed a process for producing Functionally Graded Polymeric materials (FGMs) using FP [1], polymer dispersed liquid crystals (PDLCs) via frontal curing of epoxies [2], and Interpenetrating Polymer Network (IPN) formation [3]. The very nature of FP is itself an advantage because reactions are concentrated in a very narrow region.…”
Section: Introductionmentioning
confidence: 99%